High-tech left behind? Lessons from the Ruhr cybersecurity ecosystem for approaches to develop "left behind" places - Anna Butzin; Franz Flögel (Institut Arbeit und Technik (IAT), 2022)
The attention to "left behind" places triggered a debate about alternative development approaches. Unlike prosperous regions and their prioritisation on high-tech sectors, strategies for left behind places should shift to the foundational economy, community-based social innovation and well-being. While supporting this emphasis, we see a tendency to neglect importance of research and teaching in high-tech areas for developing left behind places. Our case study in the old industrial region Ruhr shows, how unrelated initial funding for cutting-edge research sparked the development of today's cybersecurity ecosystem. The ecosystem contributes to a positive identification within the region and a dynamic start-up landscape.
Keywords: O31; O32; O180; 330; left behind places; entrepreneurial ecosystem; cybersecurity; hightech sectors; regional development